ANALISIS PEMAHAMAN MATEMATIS SISWA SMPN 3 BOJONEGORO PADA MATERI PELUANG BERDASARKAN TEORI APOS - Rista Aprillia; Ari Indriani; Dwi Erna Novianti (Journal of Technology, Mathematics and Social Science, 2022)
The research was carried out by researchers with the aim of analyzing the mathematical understanding of the students of SMPN 3 Bojonegoro on the probability material based on the APOS theory. This research method is qualitative by using a qualitative descriptive approach with the researcher acting as the key instrument or main instrument. Based on the results of the analysis of mathematical understanding of students at SMPN 3 Bojonegoro based on APOS Theory. In the framework of the action stage, the subject has a tendency to explain and present the given opportunities. Subjects in the process stage framework have a tendency to explain, present and classify questions about probability events. Subjects in the process stage framework are subjects who have a tendency to explain, present, classify and apply concepts and procedures. In the framework of the last stage, namely the framework of the schema stage, the subject has a tendency to explain, present, classify, apply and develop the concepts that have been studied. Keywords: Understanding Analysi; Mathematical Understanding; APOS Theory; Opportunity Material.